2023
DOI: 10.1242/jcs.260104
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin Y822 is an important determinant of ligand binding

Abstract: Vinculin is an actin-binding protein present at cell–matrix and cell–cell adhesions, which plays a critical role in bearing force experienced by cells and dissipating it onto the cytoskeleton. Recently, we identified a key tyrosine residue, Y822, whose phosphorylation plays a critical role in force transmission at cell–cell adhesions. The role of Y822 in human cancer remains unknown, even though Y822 is mutated to Y822C in uterine cancers. Here, we investigated the effect of this amino acid substitution and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…In 2D wound healing assay of MCF10A cells, vinculin KO cells were more efficient at closing the wound than parental cells, as previously reported using 4T1 cells (DeWane et al , 2022). KO MCF10A cells exhibited fast and directional migration towards the wound and transmitted the signal further back in the monolayer, indicating that the mechanotransduction of E-Cadherin dependent cell adhesions that vinculin provides (le Duc et al , 2010) is not essential to this transmission, and even rather inhibitory.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In 2D wound healing assay of MCF10A cells, vinculin KO cells were more efficient at closing the wound than parental cells, as previously reported using 4T1 cells (DeWane et al , 2022). KO MCF10A cells exhibited fast and directional migration towards the wound and transmitted the signal further back in the monolayer, indicating that the mechanotransduction of E-Cadherin dependent cell adhesions that vinculin provides (le Duc et al , 2010) is not essential to this transmission, and even rather inhibitory.…”
Section: Discussionsupporting
confidence: 81%
“…Vinculin belongs to both cell adhesions, the specific incorporation into cell-cell adhesions being determined by Abl-mediated phosphorylation of Y822 (Bays et al, 2014). Decreased cell-cell adhesion upon vinculin KO was recently observed in mouse 4T1 breast cancer line (DeWane et al, 2022) and is in line with the aberrant AJs between cardiac myocytes reported in heart-specific KO of vinculin in mice (Zemljic-Harpf et al, 2007). Vinculin is an essential component of cell-cell junctions that allows myosin-dependent tensile forces to develop mature junctions (Twiss et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations